Intensive treatment with ivermectin and Iota carrageenan as pre-exposure prophylaxis for COVID-19 in health care workers from Tucuman, Argentina - Chalha, Rossana E. (2021)
After COVID-19 emerged, a multitude of both novel and repurposed therapeutic agents were used empirically and studied in controlled clinical trials